Performance of Park as Public Space on the Needs, Availability, and Affordability of Services in Salatiga City (Study: Pancasila Park, Tingkir Park, Bendosari Park, and Sidomukti Park) - Rosdiana Utami, Martha; Setiawan, Bakti (Universitas Ibn Khaldun Bogor, 2023)
Park as a public space is widely recognized in the global agenda to meet the targets of sustainable development goals in SDGs 3 and SDGs 11 to make cities and settlements healthy, inclusive, resilient and sustainable through the provision of Green Open Space (GOS). The commitment of Indonesian Government related to GOS is stated in the laws, the standard states that GOS in urban areas is 30% of the total area in which 12.5% is contained as a park in every settlement scale. Currently, Salatiga City has 4 parks with an average area of below 24,000 m2 and there are several residence and settlement-scale parks with an area below 250 m2. The purpose of this study is to determine park quantity against the needs, availability, and affordability. This study used a Geographic Information System (GIS) approach with a network analysist. Data collection method used questionnaire, observation and document review. The study showed (1) Based on the comparison between the existing needs and conditions of parks from 23 sub-districts, there were 9 sub-districts that had not met it 2) Based on the network analysis, the service affordability of 4 parks was only 57.53% of the urban area that had been served by parks, most of the areas in Argomulyo District had not been served. This study is a new study on park performance assessment with spatial analysis so future park development prioritizes areas that have a value gap between existing needs and conditions and have not been afforded by park service areas. The results of this study can be taken into consideration in the future development of park with a comprehensive analysis and database.